Identification of novel biomarkers candidates for Alzheimer’s disease by bioinformatic analysis - Ferreira, Maria José Cardoso (2021)
Alzheimer's disease (AD) is the most common form of dementia worldwide, above all characterized by the emergence of senile plaques (SPs) and neurofibrillary tangles (NFTs) in the patients' brains. These two deposits are the main histopathological hallmarks of AD, and even though these are characterized by main components, like amyloid fibrils in SPs and hyperphosphorylated Tau protein in NFTs, the molecular composition of these lesions is not yet fully understood. In this work, a bioinformatics analysis of the SPs and NFTs proteomes obtained by literature review was carried out. 836 proteins were obtained for SPs and 623 proteins for NFTs, with 374 representing the common proteome. Functional analysis (Gene Ontology) of the proteomes associated with each histopathological characteristic, allowed to identify the molecular events underlying the formation of these lesions. Additionally, the analysis of proteins common to the proteomes allowed to unravel pathways that link both histopathological events and identify putative molecular targets for AD diagnostic or therapeutic intervention.